2019
DOI: 10.1080/1533015x.2019.1597661
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening their climate change literacy: A case study addressing the weaknesses in young people’s climate change awareness

Abstract: Strengthening their climate change literacy: A case study addressing the weaknesses in young people's climate change awareness,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…Varela et al (2018) found that seventh-grade students (age 12-13) developed more sophisticated mental models of climate change after a 5-day unit that included both discussion of climate science and simulated negotiation activities. Most recently, Kuthe et al (2019) found that teenagers (ages 13-16) who developed customized projects to address climate change throughout a yearlong program did not increase in their knowledge about climate change if they were disengaged with the topic. Unfortunately, these authors did not report what changes occurred among engaged students.…”
Section: Past Empirical Researchmentioning
confidence: 99%
“…Varela et al (2018) found that seventh-grade students (age 12-13) developed more sophisticated mental models of climate change after a 5-day unit that included both discussion of climate science and simulated negotiation activities. Most recently, Kuthe et al (2019) found that teenagers (ages 13-16) who developed customized projects to address climate change throughout a yearlong program did not increase in their knowledge about climate change if they were disengaged with the topic. Unfortunately, these authors did not report what changes occurred among engaged students.…”
Section: Past Empirical Researchmentioning
confidence: 99%
“…However, other authors stated that most respondents have not worried about the climate change problems (Gifford et al 2011;Weber and Stern 2011). Kuthe et al (2019) found an insignificant relationship between concern and action related to climate change. Furthermore, citizens hold different perspectives, and views vary significantly.…”
Section: The Changes In Climate-friendly Behaviour and Impact Of Climate Change Concern And Assumption Of Responsibilitymentioning
confidence: 91%
“…Organisations such as the United Nations (UN) and United Nations Educational, Scientific and Cultural Organization (UNESCO) have been stressing the need for climate change education, and this is reflected in the ever-growing significance to young people (Kuthe et al, 2020;Körfgen et al, 2017). As argued by Akrofi et al (2019), increasing student awareness through education is crucial in fostering active participation to promote climate change actions at all levels of the community.…”
Section: Climate Change and Student Involvementmentioning
confidence: 99%